Treatment Effectiveness Of Clear Aligners In Correcting Complicated And Severe Malocclusion Cases Compared To Fixed Orthodontic Appliances: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: The rapid advancement of digital orthodontics has catalyzed the adoption of clear aligner therapy (CAT) as an alternative to fixed appliances (FA) for correcting mild to severe malocclusions. However, the predictability and efficacy of CAT in complex extraction or anchorage-demanding cases remain debated.Objective: This systematic review aimed to critically evaluate and synthesize clinical evidence comparing the effectiveness, efficiency, and patient-centered outcomes of clear aligners versus fixed appliances in the treatment of complicated and severe malocclusion cases.Methods: A PRISMA-guided search across PubMed, Scopus, Web of Science, Embase, and Google Scholar identified studies published between 2008 and 2025. Ten peer-reviewed articles meeting inclusion criteria were analyzed. Outcomes included occlusal quality (OGS, PAR), treatment duration, tooth movement predictability, and oral health-related quality of life (OHRQoL).Results: Across studies, clear aligners demonstrated comparable occlusal and alignment results to fixed appliances in moderate and some extraction-based cases. Aligners yielded shorter treatment durations, improved comfort, and enhanced OHRQoL but exhibited reduced predictability in root torque, extrusion, and anchorage control. Patient satisfaction and adherence were significantly higher in aligner groups, whereas complex tooth movements often required auxiliaries or hybrid approaches.Conclusions: While clear aligners are effective for most orthodontic cases, their biomechanical limitations persist in complex malocclusions. Clinician expertise, digital planning precision, and patient compliance remain critical determinants of success.